A conferência de Martinho de Mendonça de Pina e de Proença Homem de 30 de Julho de 1733 na Academia Real da História Portuguesa, ou o primeiro ensaio pré‑científico sobre a antiguidade dos dólmenes - Cardoso, João Luís (2022)
Until the middle of the 19th century no monuments attributed to prehistoric times were identified in Europe, given that the notion of Prehistory, associated with the antiquity of the human species, only emerged by then. Notwithstanding, some 120 years before Martinho de Mendonça de Pina e de Proença, from the Royal Academy of Portuguese History, had already reached some coherent conclusions regarding prehistoric monuments, despite lacking the scientific basis that could lead to their correct interpretation. His essay on dolmens, which was the subject of the lecture he gave at the Royal Academy on July 30, 1733, embodied, 300 years ago, a genuine desire to explain the observable reality in rational terms, rejecting ancient dogmas or beliefs of religious or profane nature. This is indeed one of the most relevant aspects of his contribution, as he sought to determine antiquity of dolmens on the basis of objective criteria. To this end, he valued both the biblical information and the empirical evidence he had observed.